PENGARUH FILTER PASIF UNTUK MENEKAN HARMONISA (THD) TERHADAP UNJUK KERJA MOTOR INDUKSI 3 PHASE MENGGUNAKAN MATLAB - I Putu Yasa Darmadi; I Wayan Arta Wijaya; I Wayan Rinas (Program Studi Teknik Elektro UNUD, 2021)
In every power plant there are several power quality problems that greatly affect apower system, one of which is harmonics. Harmonics are a multiple of the basic frequency ofthe system so that the waves in the resulting system are not pure sinusoidal and in the end cancause interference with equipment in the power system, one of which is an induction motor. tosuppress the harmonic content by adding a passive filter. Simulation using the simulink methodin Matlab aims to determine changes in the performance of the 3-phase induction motor atrotation and torque by adding a passive filter to suppress the harmonic content in the network.The simulation results obtained data and in the form of wave images analyzed for differences.On the motor, there is no change in rotation, namely 1498 Rpm and torque of 0.4682 Nm.In the network there is a decrease in THD when a passive filter is added to the currents in eachphase R, S, and T, which is 1.40% with a load of 3 motors.